PENGARUH KARAKTERISTIK DAN EFEKTIVITAS KOMITE AUDIT TERHADAP MANAJEMEN LABA (Students' Journal of Accounting and Banking, 2013)
The role of audit committee is ensure the quality of corporate financial reporting process. The purpose of this paper is to examine the correlation between the characteristic of audit committees (Independency, financial expertise, activity, and time commitment) and earnings management as measured by the level of discretionary accruals. This study use data of 116 manufacturing company listed IDX in 2008 until 2010. Data of audit committees were collected from annual report. The data then analized using multiple regression analysis. The result of this study shows that audite committee skills and audit committee time comitement have influence that significant toward earnings mangement. In the meantime, others characteristic audit committee do not have significant influence toward earning managements.Keywords: audit Committee, God Corporate Governance, Earnings Management